Women and Martial Arts: A Phenomenological Study of Boxing Athletes' Perceptions - Juansah, Afda Virgine; Friskawati, Gita Febria; Karisman, Vicki Ahmad (STKIP Paasundan Press, 2024)
The purpose of this study was to provide an overview of women and sports in the perception of female athletes towards the martial sport of boxing. The population in this study were athletes and female boxing coaches of the PON JABAR team totaling 7 people. The sampling technique used is Snowball sampling so that the data taken can be complete, by taking 2 athletes and 1 coach as samples. The instruments in this study used observations and interviews. The method used in this research is descriptive qualitative method and data collection techniques by means of observation, interviews and documentation. The results of this study are with the views of people who think Boxing is a tough sport and for men. However, they ignore this view for them boxing is a cool and challenging sport and they feel fit to pursue it to achieve achievements. Based on the results of the research and discussion above, it can be concluded that women and sports are currently growing and can run in harmony. Gender is not the main barrier to achievement Gender issues seem endless which refers to equality between men and women.